2006
DOI: 10.1111/j.1365-4632.2004.02490.x
|View full text |Cite
|
Sign up to set email alerts
|

Generalized linear porokeratosis

Abstract: A 23-year-old woman was seen for widespread skin lesions present since the age of 2.5 years. Twenty years ago, she developed a brown macular lesion on her right buttock. The lesion became hyperkeratotic and subsequently spread through the posterior aspect of her right leg. It later spread to the right side of the trunk and to the right arm. When she was 9 years old, she developed similar lesions on her left arm and leg. After she was 13 years old, no new skin lesions appeared. There was no family history of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Therefore, systemic retinoids were anecdotally used for diffuse porokeratosis. 6,7 Retinoids are effective for a variety of keratinization disorders because they can reduce the turnover rate of epidermal cells. Two studies demonstrated that, after 12-week treatments for psoriasis, oral bexarotene and acitretin reduced the amount of Ki-67 stain on the lesional epidermis by 35% and 60%, respectively.…”
Section: Systematized Linear Porokeratosis: a Rare Variant Of Diffusementioning
confidence: 99%
“…Therefore, systemic retinoids were anecdotally used for diffuse porokeratosis. 6,7 Retinoids are effective for a variety of keratinization disorders because they can reduce the turnover rate of epidermal cells. Two studies demonstrated that, after 12-week treatments for psoriasis, oral bexarotene and acitretin reduced the amount of Ki-67 stain on the lesional epidermis by 35% and 60%, respectively.…”
Section: Systematized Linear Porokeratosis: a Rare Variant Of Diffusementioning
confidence: 99%
“…[ 1 ] Linear porokeratosis can be further categorized into localized, zosteriform, systematized and generalized. [ 1 2 ] Localized form is unilateral, confined to an extremity and usually distal. [ 2 ] Systematized linear porokeratosis is a disseminated variant which may be unilateral or bilateral to become a generalized form.…”
mentioning
confidence: 99%
“…[ 1 2 ] Localized form is unilateral, confined to an extremity and usually distal. [ 2 ] Systematized linear porokeratosis is a disseminated variant which may be unilateral or bilateral to become a generalized form. [ 1 ] Differential diagnoses for Blaschkoid distribution of lesions includes linear psoriasis, linear lichen planus, linear Darier's disease, and inflammatory linear verrucous nevus.…”
mentioning
confidence: 99%
“…Options include topical keratolytics, topical and systemic retinoids, cryotherapy and surgical approaches such as ablative laser surgery and curettage. Topical corticosteroids, topical tacrolimus, photodynamic therapy and imiquimod have been successful in some case reports …”
mentioning
confidence: 99%